Challenges of implementing Industry 4.0 in developed and developing countries: A comparative review - Surindra, Mochamad Denny; Caesarendra, Wahyu; Krolczyk, Grzegorz; Gupta, Munish Kumar (Universitas Muhammadiyah Magelang, 2024)
Indonesia could transform the manufacturing industry by making Indonesia 4.0, despite the many uncertainties of implementing Industry 4.0 due to high investment costs and unclear returns. Therefore, looking at neighboring countries such as Germany, the country that initiated Industry 4.0, and China, the country taking the lead in implementing Industry 4.0, it is considered essential for the manufacturing industry in Indonesia to understand how towards the revolution and identify the development of the Industry 4.0 program. Germany is confident in its capabilities in the field of manufacturing technology. It makes the main challenge in carrying out Industry 4.0 'Investment Capital, Employee Qualifications, and Security of Data Transfer and Legislation'. On the other hand, China faces significant challenges in Manufacturing Capabilities, Research and Development (R&D), and Human Capital. To adopt the transformation technology and self-assess the internal resources, Indonesia created a tool, namely the Indonesia Industry 4.0 Readiness Index (INDI 4.0). This article presents a comparative review of the Industry 4.0 readiness index from the perspective of Germany and Singapore as a developed country compared to developing countries such as China, Malaysia, and Indonesia. This study aims to provide awareness related to the readiness index, which can be used to inform industries whether they are suitable for applying Industry 4.0 and how to measure whether their employees are capable of it. In general, the INDI 4.0 measuring instrument shows the readiness of companies in Indonesia, and according to the recent assessment, the industries in Indonesia are at a moderate level, especially in the field of technology application and operation.